Prevalence of paediatric maxillo-facial trauma in India: a single centre, 5-year retrospective study - Jamwal, Tamanna; Singh, Vikas K.; Tiwari, Ruchika; Thanvi, Gaurang; Choudhary, Mahima; Gupta, Rahul (International Journal of Contemporary Pediatrics, 2022)
Background: Trauma is one of the most common reasons of fatalities worldwide. A study on the prevalence is important to know about the common causes of trauma. Such studies and data boost the campaigning on prevention and increasing awareness against trauma. Methods: Traumatised patients who reported to the emergency or casualty department of Mahatma Gandhi hospital, Sitapura, Jaipur or out-patient department of department of oral and maxillofacial surgery of Mahatma Gandhi Dental college and hospital, Sitapura, Jaipur between January 2017 and December 2021 were selected for this study. The hospital records of patients were retrospectively analysed for age, gender, etiology of trauma, distribution of fracture in facial structure and among maxilla and mandible, treatment procedures patients underwent in different age groups. Results: 371 traumatic patients were analysed for paediatric maxillofacial trauma. The commonly affected age group were found to be 13-16 years, with road traffic accidents being the most common etiology leading to mandible green stick fracture with dentoalveolar and Lefort II fracture in majority of cases. The frequent treatment option was found to be either conservative management, circummandibular wiring, splinting or Open Reduction and Internal Fixation according to age groups. Conclusions: The facial injury pattern is influenced by growth and age of patient. The effect and the management of trauma depend on the age of child. Road traffic accident are the most common cause of trauma and mandible bone is the most frequently fractured bone with dentoalveolar fracture during facial injuries. A clear male predilection has also been observed.